PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DIKELAS IV SD NEGERI 19 KAMPUNG OLO KOTA PADANG - M Harvinas Alim; Reinita; Yesi Anita; Yanti Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the improvement of learning outcomes of Pancasila Education using the Problem Based Learning (PBL) model in class IV of SDN 19 Kampung Olo, Padang City. In this study, the Classroom Action Research (PTK) type was applied using qualitative and quantitative approaches. The subjects in this study were teachers (researchers) and 13 students consisting of 4 boys and 9 girls. The results of this study showed an increase in: a) teaching modules in cycle I with an average of 83.15% (Good) and cycle II 93% (Very Good) b) implementation in the teacher aspect of cycle I with an average of 82.5% (Good) and cycle II 93% (Very Good), while implementation in the student aspect of cycle I with an average of 82.5% (Good) and cycle II 93% (Very Good), c) assessment of students in improving learning outcomes in cycle I obtained 77,3 % and cycle II with an average of 88%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve learning outcomes for Pancasila Education in grade IV.